Chinese herbal formula (GCNY)-medicated serum alleviates peroxidation induced by H2O2 in human microglial cells - Chen, Yong; Wang, Baojiang; Lai, Wing-Fu; Chen, Yanjuan; Pan, Rongbin; Tang, Zhongsheng; Liu, Dongzhou (Frontiers in Neuroscience, 2022)
Traditional Chinese herbal medicine aiming at nourishing yin formed a distinctive school of thought in history to achieve anti-aging and longevity. In the formula Gancao nourishing yin (GCNY) decoction, all of the ingredients show antioxidant properties. However, in real clinical practice, extractions of herbs are rarely applied alone but are prescribed as the integrated formula. To investigate whether GCNY possesses anti-oxidation potential, we applied GCNY to treat rats to acquire medicated serum, which was then added on H2O2 (200 μM)-modeled human microglial cell line HMC-3 in comparison with its control serum. The results revealed that GCNY-medicated serum decreased reactive oxygen species (ROS) levels. Inflammatory cytokines such as pNF-κB p65 (ser536) and IL-6 were also decreased. Nrf2 and its pathway-related molecules, such as HO1, ABCC2, GLCM, ME1, NQO1, and TKT, were activated by H2O2 modeling while declined by treating with GCNY-medicated serum, which indicated attenuated oxidative stress of GCNY. Furthermore, mRNA-seq analysis showed 58 differential expressed genes (DEGs), which were enriched in pathways including antigen processing and presentation, longevity regulation, oxidative phosphorylation, and Parkinson’s disease progression. DEGs that were downregulated by H2O2 modeling but upregulated by GCNY treatment include CENPF, MKI67, PRR11, and TOP2A. Those targets were reported to be associated with the cell cycle and cell proliferation and belong to the category of growth factor genes. In conclusion, this study verified anti-oxidation effects of GCNY and indicated its promising application for cognitive degeneration and aging-related disorders.